PENGARUH THIN CAPITALIZATION, DEBT POLICY, DAN CAPITAL INTENSITY TERHADAP TAX AVOIDANCE - Lisna Anggraini; Eka Rima Prasetya (PT. Hasba Edukasi Mandiri, 2025)
This study aims to analyze the effect of , Debt Policy, and Capital Intensity on Tax Avoidance in consumer non-cyclicals sector companies listed on the Indonesia Stock Exchange (IDX) during the 2019–2023 period. Tax avoidance is a legal strategy for companies to minimize tax burdens through loopholes in existing regulations. The method used is a quantitative approach with secondary data obtained from the company's financial statements. This study uses purposive sampling, a sample of 20 companies, and a panel data regression analysis technique processed using EViews 12 software. The results of the study indicate that Debt Policy and Capital Intensity have a significant effect on Tax Avoidance, while does not have a significant effect. Simultaneously, the three independent variables have a significant effect on Tax Avoidance. These findings can be used as consideration for tax regulators and companies in formulating fairer and more transparent tax strategies.